'We learn from our mistakes': Nursing students' perceptions of a productive failure simulation. Issue 5 (October 2022) - Palominos, Evelyn; Levett-Jones, Tracy; Power, Tamara; Martinez-Maldonado, Roberto
Abstract: Background: Productive failure simulations require students to participate in a simulation before receiving instruction. This approach contrasts with traditional simulations that typically begin with instruction followed by the simulation. Although previous studies have demonstrated that productive failure facilitates meaningful learning outcomes, students' perspectives after being exposed to this approach have not been examined in simulation-based learning. Objective: To explore nursing students' perceptions of a productive failure simulation. Design: Descriptive exploratory study. Participants: Undergraduate nursing students from one large metropolitan Australian university. Methods: Students involved in a productive failure simulation were invited to participate in semi-structured interviews on completion of their simulation experience. The interviews were audio-recorded, transcribed and the qualitative data were subjected to thematic analysis. Findings: Fifteen small group interviews and seven individual interviews were conducted (n = 66). Three themes emerged from the analysis of the qualitative data: (i) the benefits of simulation prior to instruction; (ii) the value of performing a second simulation; and (iii) the importance of normalising errors. Conclusion: The productive failure simulations helped students identify their knowledge and skill deficits and this acted as a catalyst for their learning. The normalisation of errors by the educator minimised the stress of trying to be "perfect" and assisted students to persevere despite setbacks. The provision of a second simulation helped the students rectify their errors in preparation for their future clinical practice. These aspects were considered essential for a meaningful productive failure simulation experience.